Delignification of Low-Energy Mechanical Pulp (Asplund Fibers) in a Deep Eutectic Solvent System of Choline Chloride and Lactic Acid - Pérez, Alan D.; Fiskari, Juha; Schuur, Boelo (Frontiers in Chemistry, 2021)
Deep eutectic solvents (DESs) are considered as a green and environmentally benign solvent class for various applications, including delignification of biomass. One of the major challenges in the delignification of biomass by DES is attributed to the limitations in mass transfer. By subjecting wood chips to a low-energy mechanical refining, i.e., the Asplund process, the accessible surface area increases greatly, which in turn improves the mass transfer and increases the reaction rate. In this research, the DES delignification of Asplund fibers made of Norway spruce was studied as a strategy to produce papermaking fibers under mild conditions. A DES consisting of lactic acid and choline chloride was used due to its proven performance in delignification. Various operational conditions, such as temperature, time, DES-to-wood ratio, and the type of stirring were studied. A novel parameter, Q, allowed to evaluate the impact of the operational conditions on the quality of the pulp in terms of delignification degree and fiber length. The results showed that cooking temperature had the most significant effect on the pulp quality. Additionally, it was observed that cooking times between 30 and 45 min result in a pulp yield of about 50%, while fibers have a lignin content of about 14% and a fiber length of 0.6 mm. These results demonstrate that it is possible to obtain fibers of relatively good quality from DES delignification using Asplund fibers as the starting material.